Fragmentation, Incomes, and Jobs : An Analysis of European Competitiveness - Timmer, Marcel P. (World Bank, Washington, DC, 2014)
Increasing fragmentation of production across borders is changing the nature of international competition. As a result, conventional indicators of competitiveness based on gross exports are becoming less informative and new measures are needed. This paper proposes an ex-post accounting framework of the value added and workers that are directly and indirectly related to the production of final manufacturing goods. The framework focuses on manufactures global value chain income and manufactures global value chain jobs. The paper outlines these concepts and provides trends in European countries based on a recent multi-sector, input-output model of the world economy. The analysis finds that since 1995, revealed comparative advantage of the European Union 27 is shifting to activities related to the production of nonelectrical machinery and transport equipment. The workers involved in manufactures global value chains are increasingly in services, rather than manufacturing industries. The analysis also finds a strong shift toward activities carried out by high-skilled workers, highlighting the uneven distributional effects of fragmentation. The results show that a global value chain perspective is needed to inform the policy debates on competitiveness.